The orchestra and its instruments - Headington, Christopher (Bodley Head, 1965)
Describes the development of the orchestra; explains the role of the conductor; and introduces the instruments of the string, woodwind, brass, percussion, and keyboard families, telling, for each, its history, how it is played, who introduced it, and in what compositions it is featured.